Evaluation Of Patient Radiation Dose During Orthopedic Surgery - H. Osman; A. ELZaki; B. Alamin; A. Sulieman (Asian Journal of Medical Radiological Research, 2015)
The number of orthopedic procedures requiring the use of the fluoroscopic guidance has increased over the recent years. Consequently patient exposed to un avoidable radiation doses The aim of the current study was to evaluate patient radiation dose during these procedures.37 patients under went dynamic hip screw and dynamic cannulated screw were evaluated using Thermolumincent dosimeters TLDs, under c-arm fluoroscopic machines ,in three centers in Khartoum-Sudan. The mean entrance skin dose ESD was 7.9 mGy. the bone marrow and gonad organ exposed to significant doses. No correlation was found between ESD and body mass index BMI or patient weight. orthopedic surgeries delivered lower radiation dose to patients than cardiac catheterization or hysterosalpingraphy procedures.